IMPLEMENTATION OF THE MAKE A MATCH METHOD IN ISLAMIC RELIGIOUS EDUCATION LEARNING ON STUDENTS WITH INTELLIGENCE IN SLBN SEMARANG - Alex Zukisno (Proceeding Of The International Seminar and Conference on Global Issues, 2020)
AbstractThe results showed (1) The design of the make a match learning method on the material of faith in angels can have avery good and very significant impact on the development of understanding of mentally retarded students at SLBN Semarang. (2) The implementation of the make a match method in PAI learning material Faith to angels makes an extraordinary contribution to the learning activities at SLBN Seamarang, seen from the development of understanding of mentally retarded students and also educators who teach PAI material and class teachers become more motivated and more creative in creating a pleasant atmosphere in learning. (3) The impact of implementing PAI learning material on Faith to angels on mentally retarded students at the SLBN Semarang, including: for students, they will be more active and happy in receiving learning materials, for teachers can add new scientific treasures and get new motivation to keep trying create more fun learning methods, parents are expected to be more proud and grateful, when they know their children can understand new understandings and are very useful in everyday lifeKata Kunci : Make A Match Method, Mental Retardation